TREN KEPATUHAN PAJAK PENGUSAHA UMKM DI KPP PRATAMA MERAUKE ATAS BERLAKUNYA PENGENAAN PPh FINAL ATAS OMSET - Andri Marfiana (JURNAL PAJAK INDONESIA, 2018)
The purpose of this study is to described how the implementation of PP 46, 2013 which was change by PP23, in compliance of SME’s Taxpayer. The compliancy describe in this study incline to tax revenue. However, the researcher also describe, the compliency in tax report.The result demonstrates that the implementation of PP46/PP23 tend to slightly increase the compliancy of SME’s Taxpayers. The contrbution of tax which paid by SME’s Taxpayer is not significant if compare with all tax ravanue. Eventhough, there is increasing in compliancy, in 2018, there is decreasing of tax revenue paid by SME’s Taxpayer, because in 2018, there was change from PP46 to PP23. In PP23 the tax rate was decrease, from 1% to 0.5%.In this study, it is argued that the implementation of PP46/PP23 has incresing the compliancy of SMEs Taxpayer.